Backpacking Example of Niche Tourism- Analysis of Directions of Travel with a Backpack and the Motives of Their Choice - Wojciech LEWICKI; Boguslaw STANKIEWICZ (Communications of International Proceedings, 2020)
Observed global trends in behavioural changes in the contemporary tourism market indicate a tendency of tourists to seek new active forms of spending free time, based primarily on the need to explore the world combined with new and extreme experiences. On this basis, numerous new models and forms of tourism have been identified, often referred to as "niche" tourism to distinguish it from mass tourism. One such form of niche tourism is undoubtedly Backpacking. The aim of the study is to analyse the directions of backpacking trips and motives for their selection on the example of tourists from Poland and abroad. The basis for the measurement was a survey consisting of a total of 29 substantive questions, supplemented with socio-demographic questions. The research was also conducted in two ways: as field research (July-August 2018) and via the Internet (2018-2019). In the course of the study, statements by 290 backpackers were collected The results of the research indicate that the dominant model among the inhabitants of Western Europe were long journeys (i.e. those crucial for backpackers). Also indicated the differences between Polish and foreign backpackers when it comes to motivations to return or not to return to given countries. This publication is an attempt to capture the advantages of modern Backpacking and to answer questions about the directions of travel and motives for their choice by Backpackers from Poland and abroad.
Keywords: Backpacking; Niche Tourism; Themes of Choice; Travel Destinations.